Blogging as A Space for Rhetorical Posturing on Israeli-Hezbollah War (2012)
Blogging, as a social medium, serves as a platform for individuals and organisations to produce rhetorical discourses that deserve scholarly attention. This rhetorical outlook of blogging features significantly in Middle East conflicts, as instanced in the Mideast blogs that cast their focus on the Israeli-Hezbollah war of 2006. Existing studies on blogging as a social practice seem to concentrate mainly on its social roles without paying much attention to its rhetorical outlook. This study explored the ideological nature of rhetoric in blog posts in order to establish how a comprehension of such rhetoric helps to create a better understanding of the role of blogging in the social process, especially in the context of conflict. A combination of socio-linguistic, semiotic and discourse analytic approaches, as expounded by M.A.K. Halliday’s Systemic Functional Linguistic theory, Teun van Dijk’s Triangulated Approach to discourse and Charles Sander Pierce’s semiotic theory, was adapted as the theoretical framework for the study. Ten Mideast weblogs, characterised by personal, collaborative and corporate blogs, which address the 2006 Israeli-Hezbollah conflict, and seven hundred and fifty posts, with two hundred and fifty readers’ comments, evenly distributed between the blog types, were purposively selected. The data, which are in three modes of signification -language, pictures and cartoons - were content-analysed. Bloggers employed three discourse structures - surface, schematic and dialogic – to pursue Zionist, anti-Semitic and Arab nationalistic ideologies in the posts. These three structures were arranged in a manner that got the blog readers into believing that they had made appropriate choices of response to the postings read, whereas their behaviours and opinions had been controlled through rhetorical strategies such as overstatement, understatement, metonymy, euphemism, mitigation and repetition, which all have a closer relation to underlying ideologies and belief systems of the bloggers. The surface structure contained nationalistic ideologies that were not overtly expressed but located in the linguistic and non-linguistic expressions that characterised the surface structure. The schematic structure defined the canonical order of the discourse through which topics were organised by conventional schemata such that subordinate topics were upgraded by assigning more prominence to them as headlines. The dialogic structure engaged the blog readers in imagined conversation, in which they were assigned passive role as mere commentators, whereas readers’ support was required for the credibility of the published news stories. The pattern of rhetoric in the posts was such that blog readers were made to tilt their views in support of the opinions expressed by the significations in the posts through the discourse strategies, a situation that made most comments in the posts align more with the viewpoints expressed by the bloggers. The nature of rhetoric in the Mideast posts indicates that bloggers conceal their opinions in various significations in an attempt to create strong persuasion for ideological support. The study has therefore provided the ground for establishing the Mideast blog posts as a site for readers’ manipulation in political communication, which is realised through rhetorical strategies embedded in the discourse.